Liquidity, Capital Structure, and Firm Value: The Moderating Role of Profitability in Indonesia’s Transportation and Logistics Sector - Daniy Astitri Dudi; Basuki Toto Rahmanto; Fathihani Fathihani (DEAL: International Journal of Economics and Business, 2025)
The purpose of this study was to determine the effect of liquidity and capital structure on firm value, with profitability as a moderating variable. The study population was transportation and logistics companies listed on the Indonesia Stock Exchange in 2020-2024. The purposive sampling technique involved 26 companies. The analysis method used moderated regression analysis (MRA). The results obtained in this study indicate that liquidity has no effect on firm value, while capital structure has a positive effect on firm value. Profitability moderates the effect of liquidity on firm value, but profitability does not moderate the effect of capital structure on firm value. Practically, the study provides insights for managers and investors in the transportation and logistics sector on how to balance liquidity, leverage, and profitability in order to enhance firm value and generate positive market signals. These results indicate that companies need to pay attention to liquidity, capital structure, and profitability performance to increase firm value, which will provide a signal to investors.